Optimal allocation of renewable distributed generators and shunt capacitors in distribution system using hybrid intelligent approach. (22nd June 2021) - Sudabattula, Suresh Kumar; Suresh, Velamuri; Prabaharan, N.; Sitharthan, R.; Rajesh, M.
Increased utilisation of naturally available energy sources in a distribution system (DS) is customary in recent years. These RES are intermittent in nature and impact the system performance significantly. In this paper, a methodology is utilised for bidding the lowest price to the consumer based on the availability of RES. A physical communication infrastructure between the utility and user is enabled to coordinate between the RES dominant utility and consumers. The main objectives of this communication enabled user utility interface system are to minimise power loss and enhance the voltage profile simultaneously. A multi-objective approach considering active power loss index (ALPI), voltage deviation index (VDI), and voltage stability index (VSI) are presented to solve the renewable distributed generation (RDG) and shunt capacitors (SCs) allocation problem. A combination of sensitivity analysis and random walk moth flame optimisation (RWMFO) is utilised for solving the aforementioned multi-objective function. IEEE 33 and 69 bus test systems are taken for analysis. Finally, the implemented method is compared with recent techniques available in the literature.